Pengaruh Karakteristik Individu dan Stres Kerja terhadap Kinerja Perawat di RSUD AW Sjahranie Samarinda - Ellysa Julina Lestari; Sukisno S. Riadi; Asnawati Asnawati (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
This research aim to analyse The effect of Individual Caracteristic and Work Stress to its impact on Employee Performance by using multiple linear regression analysis. Population on this research is the nurse of  RSUD AW Sjahranie Samarinda with election procedure sample use Hair method and the result is 77 respondent. Result of Hypothesis testing have shown that the Individual Caracteristic and Work Stress give significant effect to Employee Performance. In addition R2 have shown that 29,60% of Nurse Performance (Y) on RSUD AW Sjahranie had impact by Individual Caracteristic and Work Stress.Keyword: Individual Caracteristic, Work Stress, Employee Performance